Evaluating Stress-Mediated Microbial Pathogenesis in Golden Shiners, Notemigonus crysoleucas - Kaimal, Sindhu; Farmer, Bradley D.; Renukdas, Nilima N.; Abdelrahman, Hisham A.; Kelly, Anita M. (Frontiers in Physiology, 2022)
Flavobacterium covae (columnaris) is a microbial pathogen of the Golden Shiner (Notemigonus crysoleucas), a principal bait species. We investigated the effects of density and water temperature on the survival of fish subjected to a columnaris challenge and whether flow cytometry (FCM) could be a fast and reliable method to distinguish and enumerate F. covae populations from water and fish in experimental tanks. Juvenile Golden Shiners averaging 2.62 (±0.78 S.D.) g (negative for F. covae) were used in simultaneous trials at 22°C and 28°C in two ultra-low flow-through systems: each consisting of four treatments and five replicates per treatment. Treatments were fish stocked at either 600 fish/m3 or 2,400 fish/m3 and either challenged with F. covae or not; survival was observed for 48 h after challenge. Samples of water and fish tissue were obtained for FCM enumerations and validation by qPCR. No significant differences in survival were recorded between density treatments; however, high temperature and columnaris challenge treatments showed significantly higher mortality. Bacterial enumeration (number/mL) by FCM highly correlated with bacterial counts r = 0.81 (p = 0.001) in the water samples. Higher water temperatures may have increased columnaris infections and mortality in Golden Shiners. Flow cytometry is a reliable method of enumerating F. covae from experimental tank water samples.